Novel Pt/hydrophobic Modified Ceramic Catalyst Used in Room-temperature Hydrogen-oxygen Recombination Reaction - JIA Qingqing, HU Shilin, LIU Yaming (Yuanzineng kexue jishu)
Hydrogen-oxygen recombination reaction at the room-temperature has been widely used in the nuclear industry to avoid the leakage of tritium and the risk of hydrogen explosion for its high safety and low energy consumption. The key to realize the recombination reaction is to prepare the hydrophobic catalyst with excellent properties. However, current catalyst exhibits low heat tolerance, poor heat conductivity and short life. Thus, there is still a need to produce more stable and active hydrophobic catalysts, while the ceramic carrier with hydrophobic structure is expected to cover this requirement. In the reported studies, the hydrophobicity of ceramic support was usually obtained by coating with low surface energy materials, while this kind of hydrophobic ceramic carrier is no longer advantageous with the development of new hydrophobic ceramic materials. In this study, the novel hydrophobic modified ceramic was adopted as carrier to fabricate the new type of Pt/hydrophobic modified ceramic catalyst. The hydrophobic ceramic carrier was obtained by constructing the rough surface structure of CeO2 combined with the low surface energy perfluorosilane (PFOTMS) coating. Then the catalyst was prepared through impregnation method using Pt-precursor solution and H2 reduction. Compared with conventional Pt/hydrophobic ceramic catalyst which the ceramic carrier was only covered by the hydrophobic coating, the new Pt/hydrophobic modified ceramic catalyst not only makes the catalyst more hydrophobic, but also helps the prepared catalyst to obtain better combination efficiency and catalytic stability. The rough surface structure of CeO2 was proved with the high specific surface area, which could provide more sites for PFOTMS adhering to the carrier and achieving protection. Hence the hydrophobicity of the catalyst is improved, and the hydrophobic structure is almost not destroyed during the reaction process, which improves the stability of the catalyst. The rough surface structure of CeO2 could also significantly increase the specific surface area of ceramic carrier, which could help the Pt particle more uniformly deposit on the carrier resulting in increased Pt0 content and reduced Pt particle size, thereby improving catalytic activity. Meanwhile, the novel hydrophobic structure could also provide more sites for Pt particle depositing on the surface of the carrier, it could participate in the reaction preferentially than the inner Pt particle for the long process of reaction gas diffuse into the catalyst, which could also improve the catalytic activity in theory. The novel Pt/hydrophobic modified ceramic catalyst could maintain the recombination efficiency of 99.5% in the reaction time of 480 min, exhibiting improved activity and stability, which would have a good application prospect in the room-temperature hydrogen-oxygen recombination reaction.